2020
DOI: 10.1590/1518-8345.3870.3369
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ginger in reducing metabolic levels in people with diabetes: a randomized clinical trial

Abstract: Objective: to evaluate the effectiveness of ginge (Zingiber officinale) in reducing blood sugar and lipid levels in people with type 2 diabetes. Method: a randomized and double-blind clinical trial conducted with people with type 2 diabetes in primary care facilities. The study included individuals aged between 20 and 80 years old, using oral antidiabetic drugs and with HbA1c levels between 6.0% and 10%. The participants were paired 1:1, allocated in two distinct groups, and randomized in blocks, based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
0
25
3
Order By: Relevance
“…Results from a randomized clinical trial on the possible antidiabetic potential of ginger consumption suggested a decrease in blood glucose and cholesterol levels. 92 …”
Section: Miscellaneous Bioactivitiesmentioning
confidence: 99%
“…Results from a randomized clinical trial on the possible antidiabetic potential of ginger consumption suggested a decrease in blood glucose and cholesterol levels. 92 …”
Section: Miscellaneous Bioactivitiesmentioning
confidence: 99%
“…It was reported that cinnamon improved anthropometric parameters, lipid profile, and glycemic indices of type II diabetic patients ( Zare et al, 2019 ). Although the hypoglycemic effect of ginger ( Akash et al, 2015 ; Carvalho et al, 2020 ) and cinnamon ( Sahib, 2016 ; Santos and da Silva, 2018 ) administrated separately were frequently studied in both animal and human, the hypoglycemic effect of combined ginger and cinnamon administration was not sufficiently studied. Therefore, this study was designed to evaluate the effect of the combined administration of ginger and cinnamon on the glycemic, antioxidant capacity, and the structure of pancreatic islet cells in an animal model of diabetes mellitus compared to metformin and to explore the mechanism behind this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Medagama et al (42) reviewed the evidence for cinnamon and reported favorable effects of cinnamon on glucose and lipids homeostasis in individuals with T2DM. Other studies report the glucose and lipid-lowering effect of ginger and rosemary supplementation in people with T2DM (43)(44)(45)(46). Overall, data are accumulating to support metabolic benefits of H/S in humans with T2DM, although very little is known about H/S intake in at-risk individuals as a preventative strategy in disease development/transition (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%